Primeras mediciones de isótopos estables de agua y su comportamiento en fiordos de los Campos de Hielo Patagónico Sur, Chile (Revista de Biología Marina y Oceanografía, 2021)
Stable isotope measurements of seawater from fjords in the Southern Patagonian Icefields area are presented for the first time. Stable water isotope variability was associated with physiographic and oceanographic factors. Isotope depletion and lower salinity were observed at lower depths, which is consistent with shallow estuarine waters. At greater depths, the characteristics of the modified Subantarctic water mass are inferred, and the glacier proximity and temperature do not show a clear relationship with the isotopic contents. These results could be a robust basis for a possible new proxy associated with changes in water masses, freshwater mixing, and paleoclimatic studies.